p53 protein expression and risk factors in breast cancer – a retrospective study / Rashidah Shahruddin - Shahruddin, Rashidah (Institute of Graduate Studies, UiTM, 2017)
Numerous studies showed that overexpression of p53 protein may be involved in a variety of human malignancies including breast cancer. In breast cancer patients, a mutated p53 gene that encodes the p53 protein is associated with a higher risk of carcinogenesis and this study examine the potential role of p53 status in breast cancer tissues, specifically its association to established risk factors race, age, age at menarche, hormonal factors and cancer grade. The immunohistochemistry (IHC) technique was used to detect overexpression characteristics of p53 protein and the immunohistochemical results were compared with established risk factors. Analysis conducted on 111 breast tissues showed 40% (44/111) positive p53 (+) protein and 60% (67/111) nonexpression p53 (-) respectively. Malay occupied nearly half the number of respondents for overexpressed and nonexpression of p53 (+,-) protein (n=53, 48%) followed by Chinese (n=30, 27%) and Indian (n=28, 25%) with no significant difference (p> 0.05). Overexpression of p53 (+) protein occurred in 37% (41/111) of the premenopausal age group above 40 years old and 3% (3/111) in the age group less than 40 years old (p> 0.05). The probability of p53 (+) protein being overexpressed in the age group less than 40 years old is 0.66 RR 0.665(CI :0.246- 1.796) times less likely compared to age group above 41 years old.